2021
DOI: 10.7150/thno.49517
|View full text |Cite
|
Sign up to set email alerts
|

Boiling histotripsy and in-situ CD40 stimulation improve the checkpoint blockade therapy of poorly immunogenic tumors

Abstract: Background: Advanced stage cancers with a suppressive tumor microenvironment (TME) are often refractory to immune checkpoint inhibitor (ICI) therapy. Recent studies have shown that focused ultrasound (FUS) TME-modulation can synergize ICI therapy, but enhancing survival outcomes in poorly immunogenic tumors remains challenging. Here, we investigated the role of focused ultrasound based boiling histotripsy (HT) and in-situ anti-CD40 agonist antibody (αCD40) combinatorial therapy in enhancing therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…These data suggested that pHIFU exposures designed to induce mechanical damage in tissue in the absence of significant thermal change may be better equipped to create a pro-inflammatory environment than thermally ablative continuous HIFU treatments which are likely to heat fix target tissue, thus limiting intratumoral antigen release [ 16 , 19 ]. In order to facilitate clinical translation, we have used lower peak negative pressures and acoustic powers than those used in histotripsy studies [ 19 , 20 ]. Here ‘histotripsy-like’ pHIFU parameters ( P − = 17 MPa, d.c. = 1%, 10 ms exposures) that were considered ‘safe’ were chosen to avoid the induction of non-specific inflammation since treatment with higher pulse negative pressures ( P − ≥ 22 MPa), and attempts to ablate the whole tumour resulted in some skin and spleen damage.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that pHIFU exposures designed to induce mechanical damage in tissue in the absence of significant thermal change may be better equipped to create a pro-inflammatory environment than thermally ablative continuous HIFU treatments which are likely to heat fix target tissue, thus limiting intratumoral antigen release [ 16 , 19 ]. In order to facilitate clinical translation, we have used lower peak negative pressures and acoustic powers than those used in histotripsy studies [ 19 , 20 ]. Here ‘histotripsy-like’ pHIFU parameters ( P − = 17 MPa, d.c. = 1%, 10 ms exposures) that were considered ‘safe’ were chosen to avoid the induction of non-specific inflammation since treatment with higher pulse negative pressures ( P − ≥ 22 MPa), and attempts to ablate the whole tumour resulted in some skin and spleen damage.…”
Section: Discussionmentioning
confidence: 99%
“…MRgFUS technology is gaining substantial interest for its ability to provide controlled, non-invasive, and targeted therapeutic ultrasound energy, which can be adjusted to create a variety of beneficial biological effects for treatments in the brain (52). These specific effects include destructive thermal ablation (53,54), radiosensitization (55), immune activation (56,57), BBB opening for therapeutic delivery (58,59), and stem cell homing (60,61).…”
Section: Mrgfus Technology and Clinical Applicationsmentioning
confidence: 99%
“…Other recent studies found that histotripsy stimulated more potent intratumoral CD8 T cells and antigen presentation than HIFU thermal ablation in a murine breast cancer model [15] and melanoma model [16]. One recent study showed that combining histotripsy with intratumor anti-CD40 agonist antibody, αCTLA-4, and anti-PD-L1 antibody (αPD-L1) significantly improved the therapeutic efficacy against ICI refractory murine melanoma [17].…”
Section: High-intensity Focused Ultrasound Mechanical Ablation-enhancmentioning
confidence: 99%
“…As a promising therapeutic technology, FUS has the unique combined advantages of being noninvasive, nonionizing, nonpharmaceutical, spatially targeted, and deeply penetrating the body. Since 2017, five FUS modalities, including highintensity focused ultrasound (HIFU) thermal ablation [7][8][9][10][11], HIFU hyperthermia [12], HIFU mechanical ablation [13][14][15][16][17], ultrasound-targeted microbubble destruction (UTMD) [18][19][20], and sonodynamic therapy (SDT) [21,22], have been investigated in combination with ICIs for treating solid tumors in mouse models. The enhancement of antitumor immune responses by these FUS modalities demonstrated the great promise of FUS as a transformative cancer treatment modality to improve ICI therapy.…”
Section: Introductionmentioning
confidence: 99%